Pedagogical strategies for enhancing environmental education in Uzbek primary schools: a mixed-methods study - Abdumalik Kuchkinov; Sayora Tilavova; Nor Asiah Razak; Che Zalina Zulkifli; Jazira Jansaitova; Nargiz Artikova; Fazilat Khudaikulova; Bekhzod Xayridinov; Dildor Otajonova (International Journal of Evaluation and Research in Education (IJERE), 2026)
Environmental education is a fundamental component of primary science education, fostering ecological awareness and responsible behavior from an early age. Despite global recognition of its importance, the effective integration of environmental education in Uzbek primary schools faces significant challenges, including insufficient teacher competencies and limited interactive pedagogical approaches. This study investigates strategies to enhance environmental education through a mixed-methods approach involving literature analysis, questionnaires, observations, and experimental lessons. Interactive methods, project-based learning, and educational games were implemented to increase students’ ecological knowledge, practical skills, and engagement. The findings indicate substantial improvements: the proportion of students demonstrating high proficiency in environmental knowledge and practical skills increased from 23.8% to 43.3%, while those with low proficiency decreased from 48.6% to 28%. The study provides actionable insights for curriculum developers, emphasizing the integration of experiential learning and contextually relevant content; for teacher training programs, highlighting the need to strengthen pedagogical competencies in environmental education; and for policy makers, advocating systematic support for resource allocation and digital tools to enhance learning outcomes. Limitations include the regional focus and reliance on self-reported engagement measures. Future research should explore broader geographic contexts, long-term impacts, and the use of multimedia resources to further strengthen environmental literacy.